Comparison of diagnostic methods for Tetracapsuloides bryosalmonae detection in salmonid fish - Seidlova, Veronika; Syrova, Eva; Minarova, Hana; Zukal, Jan; Balaz, Vojtech; Nemcova, Monika; Papezikova, Ivana; Pikula, Jiri; Schmidt-Posthaus, Heike; Mares, Jan; Palikova, Miroslava (Journal of fish diseases, 2021)
Diagnostic accuracy of pathogen detection depends upon the selection of suitable tests. Problems can arise when the selected diagnostic test gives false-positive or false-negative results, which can affect control measures, with consequences for the population health. The aim of this study was to compare sensitivity of different diagnostic methods IHC, PCR and qPCR detecting Tetracapsuloides bryosalmonae, the causative agent of proliferative kidney disease in salmonid fish and as a consequence differences in disease prevalence. We analysed tissue from 388 salmonid specimens sampled from a recirculating system and rivers in the Czech Republic. Overall prevalence of T. bryosalmonae was extremely high at 92.0%, based on positive results of at least one of the above-mentioned screening methods. IHC resulted in a much lower detection rate (30.2%) than both PCR methods (qPCR32: 65.4%, PCR: 81.9%). While qPCR32 produced a good match with IHC (60.8%), all other methods differed significantly (p < .001) in the proportion of samples determined positive. Both PCR methods showed similar sensitivity, though specificity (i.e., the proportion of non-diseased fish classified correctly) differed significantly (p < .05). Sample preservation method significantly (p < .05) influenced the results of PCR, with a much lower DNA yield extracted from paraffin-embedded samples. Use of different methods that differ in diagnostic sensitivity and specificity resulted in random and systematic diagnosis errors, illustrating the importance of interpreting the results of each method carefully.
Keywords: parazitologie; parazitární nemoci u zvířat; Prevalence; diagnostic specificity; diagnostické testy rutinní; Česká republika; Aquaculture; prevalence; Myxozoa; řeky; Czech Republic; Rivers; pstruh; immunohistochemistry; zvířata; diagnostic sensitivity; nemoci ryb; Parasitology; polymerase chain reaction; Parasitic Diseases, Animal; Fish Diseases; Oncorhynchus mykiss; Diagnostic Tests, Routine; proliferative kidney disease; vodní hospodářství; Trout; Animals